EFEKTIFITAS KHITOSAN TERHADAP INTENSITAS SERANGAN Colletotrichum capsici PADA BUAH CABAI PASCAPANEN - Paristiyanti Nurwardani (AGROSCIENCE (AGSCI), 2011)
Effect of Chitosan to control Colletotrichum capsici on chili fruits in post harvest period wasinvestigated. Chitosan is an anti-fungi from crab or shrimp shells. Chitosan is a poly-cation polyglucosamine(the one component of fungi cell wall). The author investigated Anthracnose disease(%) and relative inhibition of anthracnose disease measured by scoring from AVRDC. Sprayingchitosan on chili fruit (harvesting time) covered the surface of chili from external factors including C.capsici . Other research investigated that chitosan inhibited conidia germination, conidiadevelopment and destroyed cell wall of hyphae of C. capsici. Chitosan layer on chili fruits surfaceinhibited penetration process by C. capsici. Effect chitosan on relative inhibition of anthracnosedisease from all treatments of chitosan were significant with control (P≤ 0.05). Chitosan 0.75%was the optimal concentration to inhibit anthracnose disease on chili fruits in post harvest period.Chitosan is a physically barrier and an antifungal for C. capsici. Chitosane 0.75% inhibitedanthracnose disease 97.58%. The mechanism of chitosane may offer the better strategy in post